Medical perspective of reproductive health education in Indonesian schoolbooks - Diarsvitri, Wienta; Utomo, Iwu Dwisetyani (Frontiers in Public Health, 2022)
The current provision for equipping young Indonesians with a comprehensive knowledge of reproductive health is inadequate. In Indonesian primary and secondary schools, reproductive health education is integrated into various subjects, including Science, Biology, Sport, and Health Education. In this paper, we compared the accuracy of the material related to reproductive health education to scientific evidence published in medical scientific journals or medical textbooks. Even though the schoolbooks were used in Indonesia's 2006 minimum standard requirements of subject matter (KTSP) curriculum, we found much inaccurate information that is not based on the scientific literature and unnecessarily detailed information on therapy and technology. Schoolbooks should emphasize promoting a healthy lifestyle, preventing high-risk sexual behaviors, encouraging openness and discussion about reproductive health in the family, improving self-confidence to refuse and avoid sexual harassment, encouraging positive sexual behaviors, and increasing awareness for treatment-seeking behavior.